A TRPA1 channel that senses thermal stimulus and irritating chemicals in Helicoverpa armigera. Issue 4 (30th March 2015) - Wei, J. J.; Fu, T.; Yang, T.; Liu, Y.; Wang, G. R.
Abstract Sensing and responding to changes in the external environment is important for insect survival. Transient receptor potential (TRP) channels are crucial for various sensory modalities including olfaction, vision, hearing, thermosensation and mechanosensation. Here, we identified and characterized a transient receptor potential gene named as HarmTRPA1 in Helicoverpa armigera antennae. HarmTRPA1 was abundantly expressed in the antennae and labial palps. Transcripts of HarmTRPA1 could also be detected in the head and proboscis. Furthermore, functional analyses of HarmTRPA1 were conducted in the Xenopus Oocyte system. The results showed that the HarmTRPA1 channel could be activated by increasing the temperature from 20 to 45 °C. No significant adaptation was observed when the stimulus was repeated. In addition to thermal stimuli, pungent natural compounds including allyl isothiocyanate, cinnamaldehyde and citronellal also activated HarmTRPA1. Taken together, we infer that HarmTRPA1 may function as both a thermal sensor involved in peripheral temperature detection and as a chemical sensor detecting irritating chemicals in vivo. Our data provide valuable insight into the TRPA1 channel in this moth and lay the foundation for developing novel strategies for pest control.